Teaching Media in the Teaching of Arabic Language/ Media Pembelajaran dalam Pembelajaran Bahasa Arab - Gemilang, Damar; Listiana, Hastuti (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2020)
This article discusses the media of learning Arabic language, through library studies that focus on distributing material effectively to students without making them boring. The limited creations and variations in learning as well as the low ability of Arabic language maharah of students make the role of the media so important. The selection of media correctly, can improve the mastery of material skills, motivate, and stimulate students. Through library studies from journals, papers, and books on learning media for the Arabic curriculum which are then analyzed and concluded data will be obtained about learning media for the Arabic curriculum which is useful for teachers. There are several rules in determining the media that will be used by taking into account the direction and objectives of learning, types of learning strategies, understanding the characteristics of the media by the teacher, in terms of cost suitability, media readiness, quality, and environment to operate the media. In terms of functions related to sensing devices, the media are divided into visual media, audio media, and audiovisual media. Meanwhile, viewed from the viewpoint in Arabic and that maharah, the media can be grouped into learning media mufrodat, nahwu-shorof, and Arabic language skills consisting of media istima', qiro'ah, kitabah, and kalam. This can help academics in applying media correctly in the learning of the Arabic language curriculum.One of the elements of learning Arabic is the student's Arabic learning strategy. But there are still some students who have not found the right strategy for learning Arabic, because of a lack of knowledge about Arabic learning strategies, especially the Oxford model of language learning strategies. The purpose of this study was to describe the implementation of the Arabic language learning strategy for students in the Oxford model of Madrasah Ibitidaiyah Al Islam Kartasura students.This research is descriptive qualitative, as for the research site at Madrasah Ibitidaiyah Al Islam Kartasura. This research was conducted from March to June 2020. The subjects in this study were students of class V A at Madrasah Ibitidaiyah Al Islam Kartasura. The informants in this study were the fifth grade Arabic teachers at Madrasah Ibitidaiyah Al Islam Kartasura. Data collection methods used were interviews, observation and documentation.The conclusion of this study is that students use Arabic learning strategies in the Oxford model because there are indications that students are using their learning. The strategies used are memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies. The strategy that is often used by students is the memorial strategy.